2007
DOI: 10.1111/j.1524-4725.2007.33251.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Nonmelanoma Skin Cancer/Keratinocyte Carcinoma: A Review of Diagnostic Accuracy of Nonmelanoma Skin Cancer Diagnostic Tests and Technologies

Abstract: Some of these new imaging technologies have the capability of providing new, three-dimensional in vivo, in situ understanding of NMSC development over time. Some of the new technologies described here have the potential to make it from the bench to the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
4
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(184 citation statements)
references
References 122 publications
(100 reference statements)
5
164
4
11
Order By: Relevance
“…It has been reported that PpIX fluorescence does not have absolute correlation to PDT outcomes 11,12 , yet it has been successfully used to detect early stages of malignant changes in the skin 29,9,30 . Measurement of fluorescence is the most widely used method employed for non-invasive in-vivo imaging of PpIX metabolism, which in turn may be used as a surrogate to optimise PDT parameters.…”
Section: Ppix Fluorescence Patterns Of Ak and Bcc Lesions And Where Pmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PpIX fluorescence does not have absolute correlation to PDT outcomes 11,12 , yet it has been successfully used to detect early stages of malignant changes in the skin 29,9,30 . Measurement of fluorescence is the most widely used method employed for non-invasive in-vivo imaging of PpIX metabolism, which in turn may be used as a surrogate to optimise PDT parameters.…”
Section: Ppix Fluorescence Patterns Of Ak and Bcc Lesions And Where Pmentioning
confidence: 99%
“…In [24] 54 lesions (21 BCCs, 22 AK, and 11 seborrheic keratosis SK) were used in the study to establish if auto-fluorescence combined with PpIX assisted fluorescence can be used for optical detection of NMSC. ALA solution was applied to the lesions and the fluorescence was imaged at 15,30,45 and 60 minutes in a dark room. They found noticeable differences between the autofluorescence in healthy and diseased skin; PpIX fluorescence increased the contrast at the lesion margins.…”
Section: Introductionmentioning
confidence: 99%
“…Although MMS provides the highest cure rates (6), the lengthy (1-2 h per layer) and costly tissue preparation procedures required for intraoperative evaluation of the excised tissues by frozen-section histopathology have limited the wider use of MMS. Apart from being time consuming, the current histopathologic methods can provide only a subjective evaluation, leading to variability in diagnosis (9,10). These drawbacks have limited the use of traditional histopathology mostly to tissue-conserving surgery of nonmelanoma skin cancers, and this technique remains impractical for most other cancer types.…”
mentioning
confidence: 99%
“…22 Yapılan gözden geçirme çalışmaları sonucunda fizik muayenenin NMCK tanısı konulmasındaki sensitivitesi %56-90 arasında tespit edilmiş olup, aradaki bu fark klinisyenin tecrübesine bağlıdır. 23 Klinik incelemenin sensitivitesi bazal hücreli karsinomların tanısında %75-90'a kadar çıkmaktadır. 23 Her ne kadar NMCK tanısının konulmasında altın standart histopatolojik inceleme olsa da NMCK'nın artan insidansı nedeni ile araştırmacılar daha az invaziv, kolay, hızlı, daha ucuz, tanı ve takipte kullanılabi-len yöntemler aramaktadır.…”
Section: Bulgularunclassified